Contre-figures du mal et transgression de l’imaginaire De William Snelgrave à Mary Prince - Malela, Buata B. (Romanica Silesiana)
This article proposes to study the theme of moral transgressions in the 18th century slave narratives by such authors as William Snelgrave, Olaudah Equiano, Gabriel Mailhol and Mary Prince. Specifically, it focuses on how these authors take a stand on the theme of evil, understood as both physical and symbolic violence inscribed in the concept of slavery. In the narratives discussed, the slaves become the figures of misfortune (and the victims of the evil), which allows the authors to re-launch the debate on the position of the Other in the French society of the Enlightenment. Key words: Slave narrative, colonialism of power, (auto)biography, slave trade, postcolonial studies.<br style="font-style: normal; font-variant: normal; font-weight: normal; letter-spacing: normal; line-height: normal; orphans: 2; text-align: -webkit-auto; text-indent: 0px; text-transform: none; white-space: normal; widows: 2; word-spacing: 0px; -webkit-text-size-adjust: auto; -webkit-text-stroke-width: 0px;" />